Peran Jurnalisme Warga dalam Mendukung Aspirasi Masyarakat (Studi Terhadap Serambinews.com) - Bustami, Bustami; Kholil, Syukur; Jufrizal, Jufrizal (Wardah, 2023)
Advances in technology and information have played a major role in advancing society. With the internet, a vast public space is formed through mass media. This has opened up opportunities for broad community participation. The rapid development of media technology and its ability to combine previous media slowly but surely influenced the practice of journalism. Therefore, Citizen journalism was born, which is a form of journalism that involves public participation in conveying information. Anyone, regardless of educational background, has the ability to plan, dig, search, process, and report information to others in any form. Serambinews.com or aceh.tribunnews.com one of the media that has opened a column of community participation in voicing ideas, ideas and opinions through the Kupi Beungoh column. This research uses a qualitative approach, which is a research method used to investigate the condition of objects naturally, with researchers as key instruments. The results showed that Serambinews.com or aceh.tribunnews.com have begun to provide opportunities for the public or the public to fill in their ideas, ideas and opinions through the Kupi Beungoh column. This column is one of the columns given to anyone to fill it in, with a note that all writing is the personal responsibility of the author. Therefore, this column is called Citizen journalism. The results showed that there was still a lack of public interest in writing their ideas and ideas through the Kupi Beungoh Serambinews.com or aceh.tribunnews.com column. This column also has weaknesses and shortcomings, because not many people know that this column is part of citizen journalism.